2010
DOI: 10.1128/jb.00488-10
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evidence for the Presence of Putative Germination Receptors in C lostridium difficile Spores

Abstract: Clostridium difficile is a spore-forming bacterium that causes Clostridium difficile-associated disease (CDAD). Intestinal microflora keeps C. difficile in the spore state and prevents colonization. Following antimicrobial treatment, the microflora is disrupted, and C. difficile spores germinate in the intestines. The resulting vegetative cells are believed to fill empty niches left by the depleted microbial community and establish infection. Thus, germination of C. difficile spores is the first required step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 45 publications
5
71
0
Order By: Relevance
“…Furthermore, mifepristone seems to be a more potent enhancer of C. sordellii spore germination and a better inhibitor of C. difficile spore germination than naturally occurring progesterone or chenodeoxycholate (39). The relevance of these findings to the clinical use of mifepristone in humans remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, mifepristone seems to be a more potent enhancer of C. sordellii spore germination and a better inhibitor of C. difficile spore germination than naturally occurring progesterone or chenodeoxycholate (39). The relevance of these findings to the clinical use of mifepristone in humans remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, pregnenolone and dehydroepiandrosterone (DHEA) also behaved as competitive inhibitors of C. difficile spore germination (data not shown). We recently reported that C. difficile spores bind chenodeoxycholate cooperatively (39). Interestingly, inhibition analysis shows no cooperativity for binding of progesterone to C. difficile spores (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The germination of spores of C. difficile by taurocholate has also been 11 reported a number of times (Giel et al, 2010;Sorg and Sonenshein, 2008;Wheeldon et al, 2008;Wilson, 1983). Although no specific receptor binding sites have been recognized in C. difficile unlike in Bacillus subtilis, a well-studied spore forming organism, it has been suggested that C. difficile possibly encode unknown receptor proteins to bind sodium taurocholate to trigger germination (Ramirez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%